ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PENINGKATAN KAPASITAS APARATUR DI ERA DIGITAL - A.M. Yadisar; Abang Zainudin; Marselina Oktavianti (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
This study analyses the factors that influence the improvement of apparatus capacity in the digital era at the Sintang Regency Regional Secretariat through a qualitative approach with an interpretative framework. Digital transformation in bureaucracy is understood not only as the application of technology, but as a social and institutional process that involves changes in competence, policy, organisational culture, leadership, and supporting infrastructure. The results show that the digital competence of the apparatus is the most dominant factor, which includes technical skills, data literacy, and adaptation to technology-based work systems. However, the level of competence is still uneven across departments. The results show that the effectiveness of capacity building is greatly influenced by human resource development policies that are integrated with the digital transformation agenda, an organisational culture that supports innovation, and visionary and transformational leadership. On the other hand, the availability and equitable distribution of information technology infrastructure are key prerequisites for the optimal use of technology by civil servants. These factors interact with each other and determine the success of capacity building in the context of government digitalisation. This study concludes that increasing the capacity of state apparatus in the digital era requires a holistic approach that integrates individual competencies, organisational policies, bureaucratic culture, leadership, and technological infrastructure. Without comprehensive integration, digital transformation has the potential to produce partial and unsustainable impacts. These findings contribute theoretically to the development of public administration studies and have practical implications for the formulation of strategies to strengthen the civil service in the digital age. It is hoped that increasing the capacity of the civil service in the digital era at the Sintang Regency Secretariat can only be achieved effectively if all supporting elements of individual competencies, organisational policies, bureaucratic culture and leadership, and technological infrastructure are strengthened simultaneously and in an integrated manner, so that they can become a strategic basis for directing the digital transformation of government towards adaptive, innovative and sustainable governance.